ANALISIS PENERAPAN STANDAR ASUHAN KEPERAWATAN DI RUANG RAWAT INAP RUMAH SAKIT UMUM PROPINSI SULAWESI TENGGARA - , I Putu Aryata Putra, dr. Tjahjono Kuntjoro, MPH, DrPH ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: In this globalized era Sulawesi Tenggara Provincial Hospital as a public health service institution is trying to improve quality of health service including nursing service. Nurses have an important role in providing quality public health service in hospital. Capability to provide professional nursing care service according to nursing standard largely depends on knowledge and motivation of nurses in implementing nursing care standard in hospital. Objective: To identify the implementation of nursing care standard at inpatient ward of Sulawesi Tenggara Provincial Hospital and association between knowledge, motivation and supervision function of head of the ward and the implementation of nursing care standard at inpatient ward of Sulawesi Tenggara Provincial Hospital. Method: The study was quantitative with cross sectional design. Population and samples of the study were all nurses at inpatient ward of Sulawesi Tenggara Provincial Hospital. Data were obtained through questionnaire and observation and analyzed using univariate, bivariate with chi square statistical test, and multivariate with logistic regression. Result: The implementation of nursing care standard at inpatient ward of Sulawesi Utara Provincial Hospital was inadequate. There was no association between knowledge and the implementation of nursing care standard